2007
DOI: 10.1074/jbc.m608898200
|View full text |Cite
|
Sign up to set email alerts
|

Myogenin and the SWI/SNF ATPase Brg1 Maintain Myogenic Gene Expression at Different Stages of Skeletal Myogenesis

Abstract: Many studies have examined transcriptional regulation during the initiation of skeletal muscle differentiation; however, there is less information regarding transcriptional control during adult myogenesis and during the maintenance of the differentiated state. MyoD and the mammalian SWI/SNF chromatinremodeling enzymes containing the Brg1 ATPase are necessary to induce myogenesis in cell culture models and in developing embryonic tissue, whereas myogenin and Brg1 are critical for the expression of the late gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 38 publications
4
77
0
1
Order By: Relevance
“…Enzyme accessibility assays have been used as a surrogate measure of such activity and have revealed, for example, Brg1-dependent changes in chromatin structure (42,52). Using such an assay, we assessed the consequence of Brg1 or Cdx2 loss of function on the chromatin structure at the Dll1 locus and found that chromatin accessibility was comparably affected by loss of either factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme accessibility assays have been used as a surrogate measure of such activity and have revealed, for example, Brg1-dependent changes in chromatin structure (42,52). Using such an assay, we assessed the consequence of Brg1 or Cdx2 loss of function on the chromatin structure at the Dll1 locus and found that chromatin accessibility was comparably affected by loss of either factor.…”
Section: Discussionmentioning
confidence: 99%
“…4, C and E). As the ATPase activity of Brg1 is essential for the chromatin remodeling activity of the SWI-SNF complex (20,22,41,42), these observations suggests that the expression of a subset of Cdx target genes depends on Brg1-mediated SWI-SNF remodeling. …”
Section: Cdx2 Interacts With Members Of the Swi-snf Complex-tomentioning
confidence: 94%
“…MRF competence to promote transcription of muscle genes relies on the interaction with the SWI/SNF chromatinremodeling complex [4,5]. SWI/SNF complex appears to mediate the unique ability of MyoD and Myf5 to remodel the chromatin and activate transcription at previously silent muscle loci [6,7], but is also required for the maintenance of muscle gene expression at later stages of skeletal myogenesis [8]. SWI/SNF complexes are composed of two mutually exclusive enzymatic subunits (the ATPases Brahma (Brm) and Brm-related gene 1 (Brg1)) and a number of structural subunits, collectively referred to as Brg1/Brm-associated factors (BAFs) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Relative histone acetylation state affects factor recruitment and/or structural changes in chromatin. The ATPase Brahma-related gene 1 (Brg1), a member of the epigenetic activators trithorax group, is also a component of the SWI/SNF nucleosome remodeling complex, and regulates neurogenesis, myogenesis, and left-right asymmetry (Seo et al, 2005;Ohkawa et al, 2006;Takeuchi et al, 2007). SWI/SNF causes nucleosomes to slide along DNA, either exposing or occluding regulatory elements that affect the transcriptional status of nearby genes.…”
Section: Histone Methylationmentioning
confidence: 99%